NNN Pincer-functionalized Porous Organic Polymer Supported Ru(III) as a Heterogeneous Catalyst for Levulinic Acid Hydrogenation to gamma-Valerolactone - Park, Kwangho; Padmanaban, Sudakar; Kim, Seong-Hoon; Jung, Kwang-Deog; Yoon, Sungho (WILEY-V C H VERLAG GMBH, 2021)
A novel porous organic polymer that incorporates NNN pincer type of ligand, i. e., 2,6-Bis(pyrazol-3-yl)pyridine, (3-bpp-POP) is prepared via solvent-knitting method. Through the characterizations, 3-bpp-POP is demonstrated to possess abundant porous structure, high surface area, and excellent thermal durability. A ruthenium molecular catalyst immobilized on the 3-bpp-POP support exhibits substantial catalytic performance for the hydrogenation of LA to GVL with an initial turnover frequency (TOF) of 1680 h(-1) and a maximum turnover number (TON) of 14762 over 24 h for LA conversion with selectivities of 91.1 % for GVL and 8.9 % for HPA. The catalyst demonstrated excellent durability during successive recycles without leaching Ru3+, which ascribe to the strong binding of pincer ligand to metal centers.
Keywords: SELECTIVE HYDROGENATION; HYPERCROSSLINKED POLYMERS; RUTHENIUM NANOPARTICLES; RU NANOPARTICLES; COMPLEXES; CONVERSION; BIOMASS; NITROGEN; DESIGN; 2,6-DI(1H-PYRAZOL-3-YL)PYRIDINE